ALLOPURINOL-INDUCED STEVENS–JOHNSON SYNDROME AND TOXIC EPIDERMAL NECROLYSIS: A CASE REPORT - CHHABRA, MANIK; GAUR, ANKIT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Allopurinol is used for the treatment of gout and related conditions; it is associated with various adverse drug reactions (ADRs) such as Stevens– Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). A 50-year-old female was presented to the emergency ward with chief complaints of reddish pinpoint lesions over the back, chest, abdomen, and lower limb-upper limb for the past 6 days. She was diagnosed with SJS. On medication interview, it was revealed that she was on allopurinol therapy, which she took 5 days back as a self-medication. The World Health Organization - Uppsala Monitoring Centre (WHO) scale was used to access the causality assessment, ADR was found to be probable. The drug was withdrawn from the therapeutic regimen of the patient. The patient was discharged after 25 days from the hospital. Allopurinol has the strongest association with SJS with TEN. There should be a screening of HLA-B 5801 antigens before commencing the allopurinol therapy to the patients.